The back of the coin in resilience: on the characteristics of advantaged low‑achieving students. - Marcenaro-Gutiérrez, Óscar David; López-Agudo, Luis Alejandro (Springer, 2021)
In the feld of Economics of Education the “resilience” term is used to designate those students from low socio-economic backgrounds who can overcome their initial situation and obtain high academic results. However, the opposite kind of student profle has been a less explored feld, i.e., high socio-economic status students who perform poorly and are thus denoted as advantaged low-achieving students. Because of that, the current study intends to disentangle the characteristics which infuence the likelihood of high socio-economic students to become low-achievers. In order to do this, we use census and longitudinal education data and a rich set of variables from secondary education students in the most populated region of Spain (Andalusia). Our results show that students’ use of time and self-confdence, together with parental engagement, when students were in primary education, are relevant variables in explaining the low achievement of advantaged students.
Keywords: Rendimiento académico; Educación - Aspectos económicos; Educación - Modelos econométricos; Advantaged low-achieving students; Census data; Longitudinal data; Andalusia